Politische Grundbegriffe im 21. Jahrhundert - Adler-Bartels, Tobias; Altenburger, Sven; Frick, Verena; Schottdorf, Tobias; Stein, Tine (Schriftenreihe der Sektion Politische Theorie und Ideengeschichte in der DVPW | Studies in Political Theory, 2023)
The dispute about political content, about the orientation and identity of a community is driven by concepts. They are the starting point of controversial interpretive difficulties and at the same time function as a heuristic framework for political science research. However, what in detail distinguishes a concept as a core political concept, how changes to such concepts take place and which factors influence the continuity of certain conceptual understandings often remain in the dark. By means of methodological and theoretical reflections, exemplary analyses of designated core concepts, investigations into the relationship between concepts and ideologies and critical interventions on contemporary conceptual politics, this book illuminates the controversial status of core political concepts. With contributions by Tobias Adler-Bartels | Sven Altenburger | Martin Beckstein | Sebastian Berg | Andreas Busen | Michael Dormal | Kimmo Elo | Michael Freeden | Verena Frick | Wilhelm Knelangen | Sara Minelli | Frank Nullmeier | Eva Helene Odzuck | Felix Petersen | Tobias Schottdorf | Karsten Schubert | Helge Schwiertz | Sandra Seubert | Tine Stein | Alexander Weiß